Advances Brought by Hydrophilic Ionic Liquids in Fields Involving Pharmaceuticals - Teresa B. V. Dinis (MDPI AG, 2021)
The negligible volatility and high tunable nature of ionic liquids (ILs) have been the main drivers of their investigation in a wide diversity of fields, among which is their application in areas involving pharmaceuticals. Although most literature dealing with ILs is still majorly devoted to hydrophobic ILs, evidence on the potential of hydrophilic ILs have been increasingly provided in the past decade, viz., ILs with improved therapeutic efficiency and bioavailability, ILs with the ability to increase drugs’ aqueous solubility, ILs with enhanced extraction performance for pharmaceuticals when employed in biphasic systems and other techniques, and ILs displaying low eco/cyto/toxicity and beneficial biological activities. Given their relevance, it is here overviewed the applications of hydrophilic ILs in fields involving pharmaceuticals, particularly focusing on achievements and advances witnessed during the last decade. The application of hydrophilic ILs within fields involving pharmaceuticals is here critically discussed according to four categories: (i) to improve pharmaceuticals solubility, envisioning improved bioavailability; (ii) as IL-based drug delivery systems; (iii) as pretreatment techniques to improve analytical methods performance dealing with pharmaceuticals, and (iv) in the recovery and purification of pharmaceuticals using IL-based systems. Key factors in the selection of appropriate ILs are identified. Insights and perspectives to bring renewed and effective solutions involving ILs able to compete with current commercial technologies are finally provided.